Designing and evaluating participatory cyber-infrastructure systems for multi-scale citizen science - Newman, Gregory John, author; Laituri, Melinda Jean, advisor; Stohlgren, Thomas J., committee member; Moore, John C., committee member; Kodrich, Kris, committee member (Colorado State University. Libraries, 2010)
To view the abstract, please see the full text of the document.
Keywords: usability; ecological data management; ecoinformatics; cyber-infrastructure; community-based monitoring; citizen science; Cyberinfrastructure -- Design; Observation (Scientific method) -- Citizen participation; Science -- Information resources management; Environmental protection -- Citizen participation